Syphilis Elimination in Indonesia by 2030: Keeping in the Right Track - Yudo Irawan; Edelyne Chelsea; Raymond Surya (Cermin Dunia Kedokteran, 2023)
Syphilis is still a global significant public health issue, including in Indonesia. World Health Organization estimated there were 7 million new syphilis infections in 2020 globally. Ministry of Health Republik Indonesia (RI) reported a total of 76,923 new cases in 2020. World Health Organization has set an ambitious target to reduce the incidence by 90% before 2030, in spite of slow global response. Syphilis elimination target in 2030 can be achieved through good cooperation between ministry of health and relevant institutions at central, provincial, and district/city levels; increasing and expanding public access to screening, diagnosis, and treatment; intensification sexually transmitted infection (STI) prevention such as health promotion, transmission prevention, surveillance, and case management; strengthening partnership and participation across sectors; increasing research and development regarding STI; and strengthening program management through monitoring, evaluation, and follow-up.   Sifilis masih menjadi masalah kesehatan publik dunia yang signifikan, termasuk di Indonesia. World Health Organization memperkirakan di dunia terdapat 7 juta kasus sifilis baru tahun 2020. Kementerian Kesehatan Republik Indonesia (Kemenkes RI) mencatat 76.923 kasus baru di tahun 2020. WHO telah menargetkan pengurangan insiden sebanyak 90% sebelum tahun 2030, meskipun respons global masih terbilang lambat. Target eliminasi sifilis tahun 2030 dapat dicapai melalui kerja sama yang baik antara Kemenkes RI dan institusi yang relevan di tingkat pusat, provinsi, dan kota/kabupaten; meningkatkan dan memperluas akses publik ke skrining, diagnosis, dan tata laksana; intensifikasi pencegahan IMS melalui promosi kesehatan, pencegahan transmisi, surveilans, dan manajemen kasus; memperkuat kerja sama dan partisipasi lintas sektoral; meningkatkan penelitian dan perkembangan terkait IMS; serta memperkuat manajemen program melalui monitoring, evaluasi, dan follow up.